Microfinance in a conflict state: Principles, strategies and challenges - Kaka, Emmanuel John; Zainal Abidin, Faudziah (2013)
Conflict leads to destruction's of life, properties and infrastructures such as markets, airports, schools, train stations, places of worships, diplomatic houses, bus stations, roads and bridges and the consequences causes outbreak of diseases and sicknesses, loss of business and jobs, leads to conflict in the host state of the refugees and create social problems and breach of law and order and consequently, increases the number of the poor people in the society. The most hit victim of conflict is the poor.Therefore microfinance institutions have to come in to support the victims with microcredit to assist them start a micro business to generate income to get them out of poverty.The aim of the study is to determine the principles, strategies and challenges face by microfinance in the states that are besiege with conflict. The source of data collection is basically documentary. The study found out that for microfinance to operate in the conflict areas, they must initiate and implement plans that will help them carry out their functions by securing their physical assets and their staff, established a data recovery and backup system, diversify their loan portfolio, expanding their services to include micro insurance and savings.Microfinance should be able to assist their customers to foresee and get ready for any disaster by encouraging compulsory deposit or savings to help the victims of conflict to have access to funds immediately.Lastly, conflict leads to decrease in productivity of the staff, revenue or income and loss of properties both physically and financial for the clients and the microfinance institutions and hence, issuance of microloan and loans repayment also decrease.